WOMEN’S POLITICAL PARTICIPATION AT THE LOCAL GOVERNMENT LEVEL: A CASE STUDY OF AKOKO SOUTH WEST LOCAL GOVERNMENT AREA, ONDO STATE, NIGERIA - Adeleke Justina Olufuunke (European Scientific Journal, ESJ, 2014)
Local government, being the nearest to the grass-root (or rural dwellers) has been described as the basic type of political arena where participatory democracy is characteristic of good governance can be achieved. But at this level of governance, women are considerably marginalized; instead, they enjoy mere tokenism at the higher level of governance and political arena where merely appointed then elected into positions such that the society is denied the advantage of their full potential as they are made to play a second fiddle to their male counterparts. Field work was conducted in relation to the importance of women’s political participation at the grass roots, factors hindering women’s political participation, and measures that can enhance women’s political participation, in Oka and Akungba in Akoko South-West Local Government Area of Ondo State Nigeria. 180 questionnaire were administered on randomly selected respondents, and the study shows that women can gain more political experience at the local level; thusenhancing their effectiveness at a higher level of decision- making, if given a chance. The study also identifies factors hindering women’s local political participation, most especially patriarchy. It finally suggests that women should be more empowered to participate at the local level to enhance their political experience for good governance and national development.